2023
DOI: 10.3389/fped.2023.1015943
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of physical activity on psychological and behavioral problems, and changes in physical activity, sleep and quality of life during the COVID-19 pandemic in preschoolers, children, and adolescents: A systematic review and meta-analysis

Abstract: BackgroundThe COVID-19 pandemic has greatly affected the level of physical activity (PA). However, little is known about its effect on health outcomes.MethodsArticles without language restrictions published from the database inception through March 16, 2022, were retrieved using the CINAHL Complete, Cochrane Library, EMBASE, Medline, PubMed, and PsycINFO databases. High-quality articles assessing the effect of PA on psychological and behavioral problems. Additionally, PA, QoL, and/or sleep problems before and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 84 publications
0
11
1
Order By: Relevance
“…The impact of the COVID-19 pandemic has affected sleep in various ways through cytokine release, neuro-inflammation, and other ways discussed later in this review. The psycho-sociological effects of social distancing, isolation, and quarantine measures manifested as loneliness, detachment, boredom, and loss of freedom [ 7 , 13 , 14 , 15 , 16 , 17 ]. This diminished coping mechanisms, which likely contributed to new mental health issues.…”
Section: How Did Covid-19 Affect Sleep: Related Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…The impact of the COVID-19 pandemic has affected sleep in various ways through cytokine release, neuro-inflammation, and other ways discussed later in this review. The psycho-sociological effects of social distancing, isolation, and quarantine measures manifested as loneliness, detachment, boredom, and loss of freedom [ 7 , 13 , 14 , 15 , 16 , 17 ]. This diminished coping mechanisms, which likely contributed to new mental health issues.…”
Section: How Did Covid-19 Affect Sleep: Related Mechanismsmentioning
confidence: 99%
“…This diminished coping mechanisms, which likely contributed to new mental health issues. As we already know, any amount of mental health concerns is an obvious link to sleep disturbances and vice-versa [ 7 , 13 , 14 , 15 , 16 , 17 ]. The increased morbidity and mortality in society further aggravated stress and led to sleep disorders.…”
Section: How Did Covid-19 Affect Sleep: Related Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another meta-analysis reported a significant drop in the frequency of moderate-to-vigorous activities and step counts for those aged from 4 to 18 years ( 6 ). A decrease in PA has been significantly associated with psychological problems, including anxiety and depression symptoms, in children and adolescents during the pandemic ( 7 , 8 ). A large meta-analysis reported that the prevalence of anxiety and depression among children and adolescents could reach 19% [95% confidence interval (CI): 14%, 25%, data from 22 studies] and 15% (95% CI: 10%, 21%, data from 16 studies), respectively ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…First, the optometry results used for diagnosing myopia were conducted under nonciliary muscle paralysis, which may have led to an overestimation of the prevalence of myopia among students. Second, our study relied on myopia data collected from 2021 to 2023, during which the COVID-19 pandemic impacted regular urban living environments, potentially introducing variations in the analysis of the role of urbanization compared with previous years . Choi et al found a correlation between the size of one’s residence and both axial length and refractive error.…”
Section: Discussionmentioning
confidence: 99%